Tourism as a Chance for Development of Peripheral Rural Areas within the Eastern Part of Lubelskie Voivodship - Joanna Szczęsna; Monika Wesołowska (Barometr Regionalny, 2015)
The peripheral rural areas of the eastern part of the Lubelskie Voivodship are very attractive in terms of their natural and cultural environment, however, despite its various tourism resources, the region’s potential in this respect is not fully exploited. The paper presents the main tourism resources of the discussed region and indicates opportunities for using them in various forms of tourism and as potential tourism products. Furthermore, the current development level of the tourism function in the region has been identified, as well as actions aimed at improving it.